(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Bone scintigraphy is highly sensitive for detecting skeletal lesions. However, it is still difficult to differentiate metastases from degenerative bone disease, especially in older cancer patients. Here, two cases are presented with chronic back pain in the background of history of cancer in which whole-body bone scans showed focal “hot spots” suspicious for metastasis. Hybrid SPECT/CT imaging clarified that these findings consistent with degenerative disease. This distinction significantly altered clinical management, avoiding unnecessary investigations and further oncologic treatment. These cases highlight the critical role of SPECT/CT in enhancing diagnostic specificity and guiding appropriate patient care. Bangladesh J. Nuclear Med. 28(2): 385-389, 2025